Assessment of slope bioengineering practice on soil hydrological regimes at Guthrie Corridor Expressway, Selangor / Aimee Halim - Aimee , Halim (2021)
The removal of vegetation and cutting of hillslopes for development has radically disturbed the balance of soil hydrological networks and resulted in slope instability or susceptibility to failure. Meanwhile, the oversupply of water flow into soils during intense or prolonged rainfall could lead to surface runoffs, which wear away the topsoil and ensue accelerated soil erosion. Accordingly, this calls for more effective slope management and bioengineering practice; hence, this study aims to address the influence of vegetation on soil hydrological components and identify the key parameters related to hydrological performances in combating slope erosion. In this study, three experimental plots were set up on the eroded cut slope at the Guthrie Corridor Expressway, Selangor, Malaysia, comprising three coverage treatments: bare (control), less dense (50% of plant coverage), and dense (80% of plant coverage) with potential pioneers of Lantana camara, Melastoma malabathricum, and Bauhinia pupurea. The study area entails sandy clay loam soil derived from the meta sedimentary rock with more quartz and weathering grade III to IV. Based on the electrical resistivity survey, the study area could contribute to slope failure due to its highly conductive characteristic, especially during intense rainfall when the water inputs into the soil are high. After two years of revegetation practice, the dense plot exhibited the highest reduction in bulk density by 52% and the highest increment in total porosity by 45.8%, thus enhancing the infiltration capacity of the slope soil. The dense plot had also positively increased the hydraulic conductivity by 73.8%, followed by the less dense plot with 30.85%. Besides, the right plant species selection and mix- culture practice displayed the best performance in soil moisture, organic matter, carbon storage, microbial abundance, and cation exchange capacity, thereby representing positive effects on soil quality and fertility. The measured erosion rate was also reduced between 10 to 15 t h-1 year−1 and this verifies a positive interaction between plant and soil, besides providing a better perspective towards the changes of soil hydrological properties. Based on the findings, L. camara in the dense plot recorded the highest photosynthetic rate, transpiration rate, stomatal conductance, and water use efficiency, followed by M. malabathricum and B. purpurea. Hence, this implies the light utilization efficiency of plants’ leaves during the photosynthesis process, which further influences the growth performance of the plants. In terms of plant hydraulic pattern, the shoot hydraulic conductance was lower than the root hydraulic conductance for all species, thereby indicating the plants’ strategy in dealing with the conflicting balance between evaporative demand and protection from hydraulic failure. Furthermore, the significant key parameters to control slope erosion through a bioengineering practice include soil porosity, fungal/bacterial ratio, soil respiration rate, soil organic matter, and plant shoot hydraulic conductance. Overall, based on the interpretation of the research results, the selection of the right pioneer species and dense vegetation coverages are decisive for the improvement of the soil-plant hydrological cycle on the selected slope, which features a notable capacity for the provision of a better slope ecosystem and promotes a promising alternative solution for slope soil reinforcement and stabilization.